Hepatic dysfunction in asphyxiated neonates: a prospective case: control study - Prasad, Rajiv; Vaghela, Vibhuti; Iyer, Radhika; Verma, Siddharth; Anadkat, Jigar (International Journal of Contemporary Pediatrics, 2021)
Background: Birth asphyxia can lead to hypoxic damage to liver at cellular level which leads to release of liver enzymes in blood as well as altered liver function. This study aimed to study the alteration of hepatic function in birth asphyxia and correlate it with different stages of hypoxic ischemic encephalopathy (HIE). Method: A case control study was conducted at SMIMER Surat which involved 115 cases and 115 controls. Cases were full term neonates admitted in the NICU with an APGAR score of 6 or less at 1 minute of birth while controls were those neonates with an APGAR score of 7 or more. Blood samples were taken at 72 hours of life and liver function tests of the 2 groups were compared. Results: The difference in aspartate transferase (AST), alanine transferase (ALT), lactate dehydrogenase (LDH), alkaline phosphatase (ALP) levels of the cases and controls were statistically significant (p<0.05). However, difference in total protein and total bilirubin in between the 2 groups was statistically insignificant. The study also found that the difference in AST, ALT and LDH was statistically significant between HIE stage 1 and stage 2 (p<0.5), between HIE stage 1 and stage 3 (p<0.5) but insignificant between HIE stage 2 and stage 3 (p>0.5). Conclusions: The present study showed that the serum levels of hepatic enzymes were higher in full term neonates with perinatal asphyxia than full term neonates without perinatal asphyxia at the age of 72 hours. The enzyme levels showed an increasing trend with increasing severity of HIE.